Conditions of Polish foreign policy in Minister Stefan Meller’s tenure (from 31 October 2005 until 9 May 2006) (Economic and Political Thought, 2016)
During the tenure of Foreign Minister Stefan Meller the decisions concerningPolish foreign policy were strongly influenced by frictions betweenparticular policy-makers and between institutions forming Polish foreignpolicy. This new situation in Polish foreign policy may be explained with theuse of Graham Allison’s decision-making models. In somewhat simplifiedterms, it may be said that S. Meller entered the government hoping that theshaping of Polish foreign policy would be based on the rational actor model.Thus, the state as a unitary actor would define the aim of foreign policy aswell as the way of its implementation, choosing the best option. The fact thatthe minister of foreign affairs was not a member of the party forming the governmentmight have been an advantage as he could have helped to unite differentgroups and build a cross-party consensus. In practice, however, Polishforeign policy became entangled in current internal political struggle, as thepolarization of the political scene between the Law and Justice Party (PiS)and the Civic Platform Party (PO) grew. The problems emerged both onthe personal plane among the main decision-makers and among institutionsforming Polish foreign policy. During the tenure of S. Meller the centre ofgravity of the rational actor model moved towards the organizational processand bureaucratic politics models. The significant increase in the importanceof internal determinants that began in 2005 should be taken into considerationin the analysis of Polish foreign policy.